Association of inflammatory and other immune markers with gallbladder cancer: Results from two independent case-control studies. (July 2016) - Koshiol, Jill; Castro, Felipe; Kemp, Troy J.; Gao, Yu-Tang; Roa, Juan Carlos; Wang, Bingsheng; Nogueira, Leticia; Araya, Juan Carlos; Shen, Ming-Chang; Rashid, Asif; Hsing, Ann W.; Hildesheim, Allan; et al.
Highlights: Inflammation markers are elevated in gallbladder cancer versus gallstone patients. Changes in local inflammation markers are generally reflected systemically in blood. CCL20, CRP, CXCL10, IL-8, resistin, and SAA had particularly robust associations. Abstract: Most gallbladder cancer (GBC) cases arise in the context of gallstones, which cause inflammation, but few gallstone patients develop GBC. We explored inflammation/immune-related markers measured in bile and serum in GBC cases compared to gallstone patients to better understand how inflammatory patterns in these two conditions differ. We measured 65 immune-related markers in serum and bile from 41 GBC cases and 127 gallstone patients from Shanghai, China, and calculated age- and sex-adjusted odds ratios (ORs) and 95% confidence intervals (95% CIs) for GBC versus gallstones. We then focused on the markers that were significantly elevated in bile and serum to replicate the findings in serum from 35 GBC cases and 31 gallstone controls from Chile. Comparing the highest versus lowest quantile, 15 markers (23%) were elevated in both serum and bile from GBC versus gallstone patients in the Shanghai study (p < 0.05). The strongest OR was for CXCL8 (interleukin-8) in serum (96.8, 95% CI: 11.9–790.2). Of these 15 markers, 6 were also significantly elevated in serum from Chile (CCL20, C-reactive protein, CXCL8, CXCL10, resistin, serum amyloid A). Pooled ORs from Shanghai and Chile for these 6 markers ranged from 7.2 (95% CI: 2.8–18.4) for CXCL10 to 58.2 (95% CI: 12.4–273.0) for CXCL8. GBC is associated with inflammation above and beyond that generated by gallstones alone. This local inflammatory process is reflected systemically. Future longitudinal studies are needed to identify the key players in cancer development, which may guide translational efforts to identify individuals at high risk of developing GBC.